The Subtle Structure Modulation of A2‐A1‐D‐A1‐A2 Type Nonfullerene Acceptors Extends the Photoelectric Response for High‐Voltage Organic Photovoltaic Cells. Issue 22 (7th February 2022) - Dai, Tingting; Tang, Ailing; Wang, Jiacheng; He, Zehua; Li, Xianda; Guo, Qing; Chen, Xingguo; Ding, Liming; Zhou, Erjun
Abstract: Molecular structural modifications are utilized to improve the short‐circuit current ( J SC ) of high‐voltage organic photovoltaics (OPVs). Herein, the classic non‐fullerene acceptor (NFA), BTA3, is chosen as a benchmark, with BTA3b containing the linear alkyl chains on the middle core and JC14 fusing thiophene on the benzotriazole (BTA) unit as a contrast. The photovoltaic devices based on J52‐F: BTA3b and J52‐F: JC14 achieve wider external quantum efficiency responses with band edges of 730 and 800 nm, respectively than that of the device based on J52‐F: BTA3 (715 nm). The corresponding   J SC increases to 14.08 and 15.78 mA cm −2, respectively, compared to BTA3 (11.56 mA cm −2 ). The smaller Urbach energy and higher electroluminescence efficiency guarantee J52‐F: JC14 a decreased energy loss (0.528 eV) and a high open‐circuit voltage ( V OC ) of 1.07 V. Finally, J52‐F: JC14 combination achieves an increased power conversion efficiency (PCE) of 10.33% than that of J52‐F: BTA3b (PCE = 9.81%) and J52‐F: BTA3 (PCE = 9.04%). Overall, the research results indicate that subtle structure modification of NFAs, especially introducing fused rings, is a simple and effective strategy to extend the photoelectric response, boosting the   J SC and ensuring a high V OC beyond 1.0 V. Abstract : Molecular structural modifications are utilized to improve the short‐circuit current ( J SC ) of the high‐voltage organic photovoltaics. J52‐F: BTA3b and J52‐F: JC14 achieve wider external quantum efficiency responses than J52‐F: BTA3 . The smaller Urbach energy and higher electroluminescence efficiency guarantee J52‐F: JC14 a decreased energy loss and a high open‐circuit voltage ( V OC ) of 1.07 V.